Exploring the Food Pairing Hypothesis in Saudi Cuisine Using Genetic Algorithm. (14th December 2021) - Al-Razgan, Muna; Tallab, Shahad; Alfakih, Taha
Abstract : Computational gastronomy has emerged as one of the recent hot research topics in the field of food science. It is a field that studies food in the era of data. One of the current research topics in this field is the food pairing hypothesis, which states that food with common flavor compounds tastes good when consumed together. The hypothesis has been studied in Western and European gastronomic societies. However, there are no reported studies conducted in Arab counterparts. In this study, we used genetic algorithms (GAs) to validate this hypothesis in Saudi cuisine. We developed a quantitative model and applied it to a dataset consisting of ingredients compounds found in Saudi cuisine recipes. Our research revealed that the pattern of ingredients occurring in Saudi dishes showed positive food pairing results like western cuisine. Moreover, our research directs the light to new dimensions where GA can be applied to explore the field of food science and computational gastronomy.